Super twisting sliding mode controller for precise ball screw driven XY positioning milling table - Jamaludin, Zamberi; Maharof, Madihah; Rashid, Ahmed Jawad; Ahmed, Sabbir; Abdullah, Lokman; Mohammad, Soleimani Amiri (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Servo drive system in positioning control requires precision, stability, and robustness against system non-linearity, un-modeled system dynamics, and input disturbance. A robust controller in a servo motor control system will realised these requirements. The objective of the work presented in this paper was to design and evaluate the performances of a Super Twisting Sliding Mode Controller (ST-SMC) for control of a ball screw driven milling table under the influence of input force disturbance. The ST-SMC control law design parameters; λ, L and W were selected using the heuristics method. The controller performances were analysed numerically using MATLAB and Simulink software based on the magnitude of the root mean square (RMSE) of the tracking errors. Reference signals with amplitude of 1 mm, 2 mm, and 3 mm at frequency of 2 Hz were selected as input signal with a random filtered white noise as the input disturbance. In case of the x-axis, results showed the precision of ST-SMC with near zero RMSE values of 0.0012 mm, 0.0093 mm, and 0.0259 mm respectively. For disturbance rejection, the percentage variation in RMSE values for cases with and without the input noise ranged from 1.5% to 29.2% compared to 15% to 42% in the case of cascade P/PI controller. The performance of the ST-SMC is to be further extended for multiple types input disturbance rejection.